Aprovechamiento de la comercialización del snack de piña deshidratada en Colombia: una mirada comparativa a los factores de oferta exportable entre regiones del país, tomando como referencia el periodo 2015 - 2019 (2021)
The research arises from the fact that a global trend towards the consumption of healthy foods is identified, where fruits play an important role, and how they have been transformed to meet the needs of demand with added value; Consequently, the objective is focused on describing how the commercialization of the Dehydrated Pineapple Snack has been taking advantage of in Colombia, taking into account the comparison of exportable supply factors between regions, taking as a reference the period 2015 to 2019 and understanding that Colombia has comparative advantages. The study method is deductive, descriptive - quantitative with a historical documentary approach, whose process consisted of three phases, starting by referring to the marketing system that Colombia has been having between 2015 and 2019, leading to identify exportable supply factors that They have excelled in a commercialization of Dried Pineapple Snack, ending with the determination of the departments that have taken advantage of transformation processes to take the pineapple fruit into Snack and at the same time highlighting the commercial relations of the department that has the greatest export with the market international